2012
DOI: 10.1371/journal.pone.0032322
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Somatotopic Maps of the Body in S1 in Rats: The Correspondence Between Functional and Anatomical Organization

Abstract: Most of what we know about cortical map development and plasticity comes from studies in mice and rats, and for the somatosensory cortex, almost exclusively from the whisker-dominated posteromedial barrel fields. Whiskers are the main effector organs of mice and rats, and their representation in cortex and subcortical pathways is a highly derived feature of murine rodents. This specialized anatomical organization may therefore not be representative of somatosensory cortex in general, especially for species tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 99 publications
6
58
0
Order By: Relevance
“…We see three possible explanations for this poor localization: (i) Hindpaw receptive fields may be insufficiently developed to generate a unilaterally localized, synchronized neuronal response. Seelke et al's recent electrophysiology study reported that although hindpaw representations are present by P10 in S1, clear topographic organization does not occur until P15, and adult-like body maps only begin to appear by P20 (31). Few studies have addressed whether neonatal somatosensory receptive fields are initially unilateral, and postnatal plasticity might suggest that fields are refined from early bilateral representations (32).…”
Section: Consequences For Interpretation Of Functional Imaging Studiesmentioning
confidence: 99%
“…We see three possible explanations for this poor localization: (i) Hindpaw receptive fields may be insufficiently developed to generate a unilaterally localized, synchronized neuronal response. Seelke et al's recent electrophysiology study reported that although hindpaw representations are present by P10 in S1, clear topographic organization does not occur until P15, and adult-like body maps only begin to appear by P20 (31). Few studies have addressed whether neonatal somatosensory receptive fields are initially unilateral, and postnatal plasticity might suggest that fields are refined from early bilateral representations (32).…”
Section: Consequences For Interpretation Of Functional Imaging Studiesmentioning
confidence: 99%
“…In rats, the highest amount of twitching can be observed during the first two postnatal weeks [13], which coincides with a period of rapid growth [1] and the emergence of adult-like motor skills [14]. Twitches occur in all skeletal muscles that have been investigated thus far, including those that control the limbs and digits [5], eyes [15], and whiskers [16], and it has been estimated that newborn rats produce hundreds of thousands of twitches each day [17].…”
Section: An Ideal Movementmentioning
confidence: 99%
“…And yet, despite the obvious importance of this sensorimotor integration, we know relatively little about where it comes from. A fine-tuned sensorimotor system cannot simply be endowed or preprogrammed; it must develop, and it must do so within the context of a continually and often rapidly changing body, with limb sizes and biomechanics changing from one day to the next [1]. How, then, do sensorimotor networks adapt to these changes?…”
Section: Introductionmentioning
confidence: 99%
“…Sensory cortex remains highly plastic throughout life, being able to modify cortical territories after major loss of input such as in sensory denervation (V Schubert et al, 2013 J Neurosci;M Kossut, 1998 Exp Brain Res) as well refining receptive fields and enhancing response amplitudes after receiving enriched input in naturalistic, or enriched, environments (Devonshire et al, 2010 Neuroscience; DB Polley et al 2004 Nature). And, whilst the changing pattern of cortical somatotopy in response to non-noxious stimuli have been mapped over post-natal development (Seelke et al, 2012), a nociceptive map has not. Seelke and colleagues (Seelke et al, 2012) included in their stimulus repertoire a stimulus identified as a "hard-tap", but it is unclear how this was presented or whether it was of noxious intensity.…”
Section: Discussionmentioning
confidence: 99%
“…And, whilst the changing pattern of cortical somatotopy in response to non-noxious stimuli have been mapped over post-natal development (Seelke et al, 2012), a nociceptive map has not. Seelke and colleagues (Seelke et al, 2012) included in their stimulus repertoire a stimulus identified as a "hard-tap", but it is unclear how this was presented or whether it was of noxious intensity. Furthermore, this study mapped cortical neuronal responses only in as much determining somatotopic cortical representation, rather than how the intensity of that stimulus is encoded within S1 and whether this changes with age; this leaves important unanswered questions regarding the development of functional responses to nociceptive stimuli in the cortex.…”
Section: Discussionmentioning
confidence: 99%